Multi-Disaster Risk Analysis of Klaten Regency, Central Java, Indonesia - Candra Dian Lukita Tauhid; Teuku Faisal Fathani; Djoko Legono (Journal of the Civil Engineering Forum, 2017)
Klaten Regency is located in Central Java Province, Indonesia, ranked as 19th most susceptible area in Indonesia. Among of many disasters those take place in Klaten are floods, landslides, and earthquake, which cause damages and loss of lives. Unfortunately, some areas in Klaten Regency are also very vulnerable to the disasters that often contribute severe damage and loss. This paper presents result of risk analysis due to floods, landslides and earthquake disaster at Klaten Regency. Several parameters or criteria are utilized to describe the level of the disaster intensities. The flood susceptibility parameters are the Topographic Wet Index (TWI), Normalized Difference Vegetation Index (NDVI), permeability and roughness, as proposed by Kafira, et al. (2015). The landslide susceptibility are the geology, slope, elevation, distance from fault, distance from rivers, rainfall and land use, as suggested by Thearith (2009) whereas the earthquake susceptibility was referred to FEMA P-154 by using the Ss and S1. The vulnerability and risk analysis are carried out by referring to the parameters as stipulated by the Chief Regulation of the National Board of Disaster Management No.2 Year 2012 (Perka Badan Nasional Penanggulangan Bencana- BNPB), concerning the parameters being used for the vulnerability analysis, i.e. population density, poverty ratio, land use, and level of Gross Regional Domestic Product. Further spatial analysis of the risk performs the multi-disaster risk map as a combination between the floods, landslides and earthquake disaster risk in Klaten Regency. The established multi-disaster risk map shows the risk level in the Klaten Regency, i.e., 16.31% at very low risk, 33.01% at low risk, 34.49% at medium risk, at 14.22% high risk and 1.97% at very high risk.